Analisa Dan Perancangan Sistem Informasi Akademik MI Nurul Hidayah Dengan Menggunakan Metode Rapid Application Development - Rita Yulianti; Sifa Nafista Hairul Rozak; Muhammad Nur Fauzi; Firmansyah; Aries Saifudin (Shofanah Media Berkah, 2023)
The creation of educational services at MI Nurul Hidayah School has experienced obstacles and errors in the administrative process. To overcome these problems, it is necessary to implement an information and technology system that is computerized, fast, precise, and accurate.By implementing a good information system and technology, schools can automate the submission and administration process. This will help in making reports and administrative services that are fast and precise, reduce the time required by students in the administrative process, and minimize errors that may occur. The application of computerized information systems and technology will help replace or improve manual processes that are prone to human error. This system will help manage data more efficiently, increase accuracy, and reduce the risk of administrative errors.The academic information system is a solution that can help overcome problems in the world of education, especially in organizing workflows in academic institutions. By utilizing information technology, this system can support operational activities in the field of education. The academic information system created at MI Nurul Hidayah School has the main objective to facilitate users, especially teachers and students, in managing school academic data. The data includes grades, attendance, and financial information. With this system, it is expected that the academic data management process can be more efficient and structured. Based on the research and testing conducted, it can be concluded that 80.25% of respondents stated that this application is feasible to use to assist users in processing school academic data. This shows that the majority of respondents feel this system is useful and can meet their needs. However, 19.75% of respondents stated that this application still needs to be developed again. This indicates that there are still some shortcomings or features that need to be improved or added in this academic information system. Feedback from respondents who consider the need for redevelopment can be the basis for making improvements and improvements to the system. Overall, the use of the academic information system at MI Nurul Hidayah School can provide benefits in managing academic data. However, it is important to continue to evaluate, develop and improve so that this system can continue to meet user needs and make an optimal contribution to education.